Pengaruh Pembelajaran Model Discovery Learning terhadap Aspek Kognitif Peserta Didik - Zuhdi, Rasyid; Utami, Fithria (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine the effect of using discovery learning models on improving the cognitive aspects of students. Discovery learning model emphasizes mental processes where students can assimilate a concept or principle with the result that discovery learning model can make students more active, think critically and develop creativity and make students more independent. This study used an experimental research design with a Pretest Posttest Control Group Design. The sample in this study were students at the junior high school level, VIII A as the control class and VIII B as the experimental class, amount 68 students and selected using cluster random sampling technique. The control class and the experimental class have passed the prerequisite test, namely the normality test and homogenity test. The normality and homogenity tests were assisted by the SPSS application which showed a significance value in the normality test of Sig. 0.703> 0.05 in the control class, the significance value of Sig. 0.473> 0.05 in the experimental class, the homogeneity test showed a significance value of Sig. 0.805 > 0.05. Thus it can be said that the class is normally distributed and is homogeneous. The instruments used in this study used pretest and posttest question sheets. Study result data were analyzed using the Independent Sample t-Test at a 5% level of confidence using the SPSS application. This study gave the results of the cognitive aspects in the experimental class significantly different from the cognitive aspects in the control class, with a significance value of Sig. (2-tailed) 0.045 < 0.05. Thus it can be said that the use of discovery learning models has a significant effect on the cognitive aspects of students. Keywords: discovery learning, cognitif, students